Counseling and Assistance in Handling Chemical Hazards in Fresh Food Using Aquaponics in Pulau Busuk Village Kuantan Singingi Regency: Penyuluhan Dan Pendampingan Penanganan Bahaya Kimia Pada Pangan Segar Dengan Aquaponik Di Desa Pulau Busuk Kabupaten Kuantan Singingi - Desta, Desta Andriani; Seprido, Seprido; Andri, Alsar (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Serving healthy and nutritious food must be balanced with the safety of the food source served. Various reports show the existence of chemical hazards in food, especially fresh food such as vegetables and fruit. Education on controlling chemical hazards in fresh food needs to be improved for housewives who serve food in the household. This outreach activity was carried out in the village of Pulau Buuk involving 20-30 housewives. The method used is lectures and discussions by providing educational material to housewives. To evaluate the results of this service using pre- and post-test surveys. The results of this outreach activity can increase housewives' knowledge regarding handling chemical hazards in fresh food. Around 62% of participants understand how to handle chemical hazards in fresh food, and the remaining 38% of participants understand how to handle chemical hazards in fresh food. These findings indicate that education about handling chemical hazards in fresh food using aquaponics can increase public awareness of family health and family food safety.